High temperature sublimation of α-amino acids: a realistic prebiotic process leading to large enantiomeric excess. Issue 32 (25th March 2015) - Tarasevych, Arkadii V.; Sorochinsky, Alexander E.; Kukhar, Valery P.; Guillemin, Jean-Claude
Abstract : Reiterative high temperature co-sublimation of mixtures of racemic amino acids in the presence of an enantioenriched derivative leads to high enantiomeric excesses with a sense of the handedness identical to that of the enantioenriched starting material. Abstract : The reiterative high temperature co-sublimation of an enantiopure or an enantioenriched α-amino acid mixed with racemic α-amino acids leads to deracemization of the latter. A synergistic effect is observed for complex mixtures, and the sense of the handedness is, for all compounds, identical to that of the enantioenriched starting material.